2017
DOI: 10.11152/mu-942
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Radiation Force Impulse (ARFI) Elastography for non‑invasive evaluation of hepatic fibrosis in chronic hepatitis B and C patients: a systematic review and meta-analysis

Abstract: Aim: The purpose of the study was to assess the effect of Acoustic Radiation Force Impulse (ARFI) elastography in the diagnosis of liver fibrosis in chronic hepatitis B and C patients through Meta-analysis. Material and methods: Four databases (PubMed, the Cochrane Library, WanFang data, and CNKI) were searched. The key words were: (“ARFI” or “acoustic radiation force impulse”) combined with “liver fibrosis” and (“chronic hepatitis” or “HBV HCV”). Heterogeneity (I2) was assessed, and its source was analyzed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 39 publications
2
43
0
4
Order By: Relevance
“…In our ROC analyses, AUCs of VTQ for LF in the CHB cohort and the CHC cohort ranged from 0.75 to 0.90 and 0.78 to 0.88, respectively. Virtual touch quantification had strong P ‐values for predicting the severity of LF in most of the multivariate analyses, which were in line with previous reports . A recent study compared three elastographic methods, transient elastography, 2‐D shear wave elastography, and ARFI‐VTQ, in CLD patients and no notable differences in diagnostic accuracy were observed among them for the severity of LF .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In our ROC analyses, AUCs of VTQ for LF in the CHB cohort and the CHC cohort ranged from 0.75 to 0.90 and 0.78 to 0.88, respectively. Virtual touch quantification had strong P ‐values for predicting the severity of LF in most of the multivariate analyses, which were in line with previous reports . A recent study compared three elastographic methods, transient elastography, 2‐D shear wave elastography, and ARFI‐VTQ, in CLD patients and no notable differences in diagnostic accuracy were observed among them for the severity of LF .…”
Section: Discussionsupporting
confidence: 88%
“…Currently, one of the major ultrasound‐based assessment methods for LF using shear wave velocity is acoustic radiation force impulse (ARFI) . Several meta‐analyses and systematic reviews confirmed clinical utility of ARFI for the evaluation of the severity of LF . Usefulness of ARFI elastography is reported in not only CLDs but also chronic kidney diseases .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, compared with conventional elastographic techniques, ARFI elastography provide quantitative measurements of SWV, which might be superior in evaluating the grade of hepatic fibrosis [14,17]. The effects of ARFI elastography in staging hepatic fibrosis have been extensively studied with several meta analyses been published, especially regarding chronic hepatitis [1,6,[17][18][19]. However, limited data are available on the performance of ARFI in staging liver fibrosis in non-alcoholic fatty/alcoholic liver diseases (NAFLD/ALD), non-alcoholic steatohepatitis (NASH), patients with liver transplantation or other autoimmune-related diseases (such as primary biliary cirrhosis, PBC), etc.…”
Section: Introductionmentioning
confidence: 99%
“…It can be performed in a periodic follow-up and is generally superior to other serological modalities [12][13][14]. In a meta-analysis study, ARFI demonstrated a satisfactory ability to predict higher-stage liver fibrosis (F = 3) and liver cirrhosis (F = 4) [15]. However, inflammation, variation, and other factors have significant impacts on the interpretation [16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%